Cluster-Based Policy Making: Assessing Performance and Sustaining Competitiveness - Aziz, Kamarulzaman Ab.; Norhashim, Mariati (JOHN WILEY & SONS INC, 2008)
Tremendous changes in technology, political and social frameworks, as well as the impacts of globalization, have put pressure on countries to become competitive. One strategy for creating an engine of economic growth is the creation of clusters. These clusters, be they naturally or artificially conceived, hold the promise of becoming the economic weapons of a country. Many studies have been done to understand the factors behind the successes and failures of clusters. One of the reasons behind the inconsistent success of existing cluster policy frameworks in managing cluster performance is the fact that clusters often are at different levels of development, and it will require different strategies to create, enhance, and sustain their competitive advantage. This paper aims to propose and demonstrate a more holistic framework designed to understand key cluster dynamics that drives cluster performance, which then will enable policy makers to work toward ensuring sustainable cluster development.